Self-mode-locking and self-phase modulation in Tm3+-doped double clad fiber laser for pulse peak power enhancement and multi-wavelength generation. (September 2021) - Zhang, Huiru; Zhang, Jiaji; Sun, Shengzhi; Wu, Duanduan; Zhao, Ruwei; Wang, Rongping; Dai, Shixun
Abstract: A dual frequency mode-locked Tm 3+ -doped double clad fiber laser (TDCFL) is proposed by combining self-mode-locking with self-phase modulation (SPM) effect. The SPM effect stimulates the 24th harmonic mode-locking operation. The unpumped gain fiber-based self-mode-locking effect initiates the fundamental mode-locked operation. This fundamental mode-locked pulse acts as a modulation envelope of the 24th harmonic one. In this situation, the maximum pulse peak power and the largest pulse energy improve greatly. Its maximum pulse peak power is at least 311 times higher than the fundamental mode-locked one. And the difference of pulse energy is 7.8 times. Furthermore, this dual frequency mode-locked TDCFL generates multi-wavelength light under high pump power. These results could offer an exciting new prospect for obtaining simple, compact and high performance multi-wavelength mode-locked fiber lasers.